Mountain temples & temple mountains : architecture, religion, and nature in the central Himalayas - Chanchani, Nachiket (New Delhi Niyogi Books, 2021)
Arguing for parallels in temple architecture and evolving places of pilgrimage in both the Central Himalayas and more distant places such as Gujarat, NachiketChanchani introduces hitherto less explored aspects of potential connections to enrich studies of early medieval India.
Keywords: Himalaya Mountains Region; Hindu pilgrims and pilgrimages; Hindu temples